High-Salt Diet Causes Sleep Fragmentation in Young Drosophila Through Circadian Rhythm and Dopaminergic Systems - Xie, Jiayu; Wang, Danfeng; Ling, Shengan; Yang, Guang; Yang, Yufeng; Chen, Wenfeng (Frontiers in Neuroscience, 2019)
Salt (sodium chloride) is an essential dietary requirement, but excessive consumption has long-term adverse consequences. A high salt diet (HSD) increases the risk of chronic diseases such as cardiovascular conditions and diabetes and is also associated with poor sleep quality. Little is known, however, about the neural circuit mechanisms that mediate HSD-induced sleep changes. In this study, we sought to identify the effects of HSD on Drosophila sleep and related neural circuit mechanisms. Strikingly, we found that HSD causes young Drosophila to exhibit a fragmented sleep phenotype similar to that of normal aging individuals. Importantly, we further showed that HSD slightly impairs circadian rhythms and that the HSD-induced sleep changes are dependent on the circadian rhythm system. In addition, we demonstrated that HSD-induced sleep changes are dopaminergic-system dependent. Together, these results provide insight into how elevated salt in the diet can affect sleep quality.